Basic Handball - Methods - Tactics - Techniques - Czerwinsky, J.; Taborsky, F. (European Handball Federation, 1997)
I. THE CHARACTERIZATION OF THE HANDBALL GAME 2 II. THE DEVELOPMENT OF HANDBALL IN THE WORLD 2 III. METHODICAL INTRODUCTION 3 The Rules of Teaching 3 1. The Rule of Visual Teaching 3 2. The Rule of Regularity 4 3. The Rule of Awareness and to Be Active in Learning 4 4. The Rule of Step by Step Teaching 4 5. The Rule of Versatility 4 6. The Rule of Fixation 4 The Methods of Teaching 4 1. Analytic Method 4 2. Synthetic Method 4 3. Complex Method 4 The Forms of Teaching 4 1. The Form of Games and Pre-Games 4 2. The Strict Form 4 3. The Form of the Fragments of a Game 5 4. The Form of a Game: Simple,Educational and Basic 5 The Stages of Teaching a New Element 5 1. The Stage of Generalization 5 2. The Stage of Concentration 5 3. The Stageof Automation 5 The Rules for Teaching Beginners 5 A Physical Education Lesson 5 A Lesson Draft 6 IV. TECHNIQUE 6 General Remarks 6 Catching the Ball 7 1. General Remarks 7 2. Various Catching Methods 7 Passing 7 1. General Remarks 7 2.Types of Passing 7 Teaching of Catching and Passing 8 1. General Remarks 8 Shooting 8 1. Shot in Place 9 2. Leaning Back Shot 9 3. Vertical Jump Shot 10 4. Stride Jump Shot 10 5. Shots While Falling 10 Teaching of Shots 12 Dribbling 13 Teaching of Dribbling 13 Feints 13 1. Body Feints 13 2. Ball Feints 13 3. Performance of Feints 14 Teaching Feints 16 A Player`s Movement in Offence and Defence 16 1. Individual Defence Elements 16 2. Individual Defence Technical Elements 17 3. Stealing the Ball 17 4. Screening the Opponent without a Ball 17 5. Screening with a Ball 17 Teaching of Individual Defence 18 Goalkeeper 19 1. General Remarks 19 2. The Goalkeeper`s Play 19 3. Physical Conditioning 22 4. The Game Tactics 23 Teaching of the Goalkeeper`s Game 25 1. Posture and Footwork 25 2. Defending with Legs and Hands 25 3. Passing to Initiate Fast Attack 27 4. Speed of Reaction 27 V. TACTICAL MEANS 28 Individual Tactical Methods 28 1. Always to Be Held True 29 2. For the Players in Attack 29 3. For the Players in Defence 29 4. For the Goalkeepers 30 5. In Conclusion for All 30 Group and Team Tactical Methods 30 1. Bases of Cooperation in Attack and Defence 30 2. Transition to Attack 31 3. Transition to Defence 32 4. Attacking Systems 33 5. Defensive Systems 34 6. An Example of the Pratice of a Playing System 35 7. Involvement of Chosen Shooting Combinatons 40 8. Concluding Notes 44